Utilization of Rice Bran Fermentation with Aspergillus niger on Feed Raw Material of Tilapia (Oreochromis niloticus) - Mochammad Ikhwanuddin; Achmad Noerkhaerin Putra; Mustahal Mustahal (JURNAL PERIKANAN DAN KELAUTAN, 2018)
Tilapia (Oreochromis niloticus) is a type of aquaculture commodity that has high economic value. This research aims to know the effect of feeding of rice bran fermentation on feed raw material to the parameter digestibility and growth of tilapia. The used tilapia were sized 5.33 ± 0.00 g/fish with stocking density 15 fish/40 L (aquarium). Fish were fed three times daily in ad satiation. This study used three treatment with four replications, namely (A) commercial feed as control, (B) commercial feed with the addition of rice bran fermentation with Aspergillus niger, (C) commercial feed with the addition of rice bran without fermentation. The results showed that the feed (B) can improve nutrient digestibility and growth of tilapia with dry matter digestibility of 67,87 ± 2,44 %, protein digestibility of 85.04 ± 3.28 %, feed intake of 230 ± 4.08 g, final weight 11.81 ± 0.45 g, specific growth rate of 1.65 ± 0.40 % and survival rate of 75.00 ± 0.11 % compared to the other treatments